Comparative analyses and implications for antivenom serotherapy of four Moroccan scorpion Buthus occitanus venoms: Subspecies tunetanus, paris, malhommei, and mardochei. (July 2018) - Emerich, Bruna Luiza; De Lima, Maria Elena; Martin-Eauclaire, Marie-France; Bougis, Pierre E.
Abstract: Temporary passive immunity such as serotherapy against venoms requires the full knowledge of all venom's components. Here, four venoms from Moroccan common yellow scorpions belonging to Buthus occitanus, subspecies tunetanus, paris, malhommei, and mardochei, all collected in four different restricted areas, were analysed in deep. They were fractionated by reversed-phase high-performance liquid chromatography (RP-HPLC) and their molecular masse profile determined by off-line MALDI-TOF mass spectrometry. Characterisation of their main components was achieved by enzyme-linked immunosorbent assay (ELISA) using specific antisera against the major lethal scorpion toxins identified so far, i.e. voltage-gated sodium channels (Nav ) modulators α- and β-toxins, as well as diverse potassium channel pore blocker toxins. For fractions with identical RP-HPLC retention times, we observe that their relative quantities show large differences. Moreover, identical masses present simultaneously in the four venoms are infrequent. ELISAs show that the majority of the RP-HPLC compounds cross-react with the antiserum against the "α-like" toxin Bot I, which has been previously identified in the Algerian Buthus occitanus tunetanus venom. Moreover, minor fractions were recognised by the antiserum against the highly lethal "classical" α-toxin of reference AaH II from the Androctonus australis venom. As such, our results bring new sights for further improving scorpion venom serotherapy in Morocco. Graphical abstract: Image 1 Highlights: Four subspecies of Moroccan Buthus occitanus scorpion venoms were studied. Biochemical profiles were set up by RP-HPLC and MALDI-TOF mass spectrometry. ELISAs reveal lethal Nav channels and Kv channel pore blocker toxins. "Classical" α-toxin group II and "alpha-like" toxin group III were identified. Our results bring new insights for improving scorpion serotherapy in Morocco.